Indirect optical transitions from carriers trapped on the delta doping and on the parabolic quantum well - Tabata, Américo Sheitiro [UNESP]; Oliveira, José Brás Barreto de [UNESP]; Pintão, Carlos Alberto Fonzar [UNESP]; da Silva, E. C. F.; Lamas, T. E.; Duarte, C. A.; Gusev, G. M. (Elsevier B.V., 2012)
In this work, doped AlGaAs/GaAs parabolic quantum wells (PQW) with different well widths (from 1000 angstrom up to 3000 angstrom) were investigated by means of photoluminescence (PL) measurements. In order to achieve the 2DEG inside the PQW Si delta doping is placed at both side of the well. We have observed that the thickness of this space layer plays a major rule on the characteristics of the 2DEG. It has to be thicker enough to prevent any diffusions of Si to the well and thin enough to allow electrons migration inside the well. From PL measurement, we have observed beside the intra well transitions, indirect transitions involving still trapped electron on the delta doping and holes inside the PQW. For the thinness sample, we have measured a well defined PL peak at low energy side of the GaAs bulk emission. With the increasing of the well thickness this peak intensity decreases and for the thickest sample it almost disappears. Our theoretical calculation indicated that carriers (electron and holes) are more placed at the center of the PQW. In this way, when the well thickness increases the distance between electrons on the delta doping and holes on the well also increases, it decreases the probability of occurrence of these indirect optical transitions. (C) 2012 Published by Elsevier B.V. Selection and/or peer-review under responsibility of Universidade Federal de Juiz de Fora, Brazil.
Keywords: semiconductor; photoluminescence; parabolic quantum well